Length relationships between vertebral column and spinal cord: differential contributions of the cervical, thoracic and lumbosacral regions - Glaudot, Guillaume; Nunès, Anthony; Lété, Aegryan; Lengelé, Benoît; Behets, Catherine; Jankovski, Aleksandar (Surgical and radiologic anatomy (English ed.), 2025)
Purpose The localization of the human spinal cord (SC) segments remains a challenge without thorough post-mortem analysis and their relationship with the vertebrae has long been investigated. In this post-mortem study, we assessed the relationship between the cervical, thoracic, lumbar and sacral lengths of the SC and of the vertebral column (VC). Methods Twenty human SCs were extracted from the vertebral canal. The cervical, thoracic, lumbar and sacral regional lengths of SC and VC were measured by two examiners. Statistical analyses included t-test, ANOVA, Fisher’s exact test, Kruskal–Wallis H-test and Pearson’s correlation test. Results No significant relationship was found between the sex of the subjects or the total SC length and its caudal limit in the vertebral canal. The length of the thoracic SC was significantly different between 3 groups of short, intermediate and long SCs, while no significant difference was observed in the lumbar and sacral SC regions. Highly significant correlations were observed between the thoracic SC length, on the one hand, and the total SC length, the thoracic VC length and the total VC length, on the other hand. The very constant length of the lumbar and sacral SC regions was not correlated with any regional SC or VC lengths. Conclusion This study confirms the constant length of the lumbar and sacral SC regions, independently of any other regional SC and VC measurements, while the thoracic region of the SC appears to be the main contributor in the variation of the total SC length.